Evaluating Public Services Delivery on Promoting Inclusive Growth for Inhabitants of Industrial Cities in Developing Countries - Saniya Siddiqui; Mohammad Nadeem Akhtar; Jamal K. Nejem; Mastour Saud Alnoumasi (Salehan Institute of Higher Education, 2021)
It has been debated that effective essential public services delivery is crucial to inculcate inclusive growth in cities over the past decades. Cities continue to be central to the debate; however, the current study focuses on industrial towns. As industrial towns' development around cities attract investment and promote economic growth, the present research studies the impact of essential public services delivery on promoting inclusive growth for inhabitants of industrial towns in developing countries. Human Capabilities Dimension Approach and its parameters (Social and Physical Infrastructure) have been employed to explore the role of basic amenities in transferring growth levels across all population sections. The idea explored is studied through Mandideep Industrial Town's case study, where six parameters (Physical and socioeconomic status, water supply, sanitation, health care facilities, education facilities), and perceived inclusive growth have been considered for data collection and analysis. Indicators under each parameter are analyzed based on the 4A's-Availability, Accessibility, Awareness, and Affordability. Site selection revolved around a city reconnaissance survey and Household survey for 200 households. Aggregated analysis for the city and ward-wise comparative analysis and statistical correlation tools were used to establish a relationship between basic public services delivery and perceived inclusive growth. The research aims to study and establish a correlation between public service delivery and perceived inclusive growth by the industrial town's inhabitants. Discussions following data analysis led to recommendations for city and ward-level. The importance of efficient service delivery for increased perception of inclusive growth is established. Along with the six parameters considered for the study, physical and environmental planning emerge as crucial parameters that impact other public services for enhanced inclusive growth in industrial cities. Doi: 10.28991/cej-2021-03091648 Full Text: PDF